Shape Cognition and Temporal, Instrumental and Cognitive Constraints on Tonality. Public Peer Review of “Tonality: The Shape of Affect” by Mine Doğantan-Dack. - God, Rolfe Inge (Empirical Musicology Review, 2013)
One of the main aims of Mine Doğantan-Dack’s article is to present a theory of the evolutionary emergence of tonality in music and its connections with affective states. In the course of her article, we are presented with several fundamental issues of music perception, music and evolution, dynamical theory, as well as music and shape. In this public peer review, I comment on some of these issues, starting with some thoughts on the relationships between musical features, shapes and timescales, then continue with some thoughts on tonality, and finally present some remarks on tonality in relation to instrumental and human constraints.